Um estudo sobre a metonímia como um processo cognitivo - Santos, Ione Aires (2011)
Looking metonymy unravel and understand it, in this work, it is a study of the figurative language in a quality look, from rhetoric to get to the investigative course on the theoretical assumptions of Cognitive Linguistics. For this, the imagery is seen in Aristotelian rhetoric and in traditional grammars. Makes a comparison between metaphor and metonymy in the traditional approach, and verify how the taxonomy of metonymy, as it is presented in textbooks and what the consequences of traditional taxonomic approach. Knowing the implications of the study on traditional metonymy, presents the Cognitive Linguistics, a discipline that has brought a new perspective on the epistemological way things are experienced and categorized. We present the metaphor and metonymy in the view of cognition and, ultimately, it is the study of metonymy relevant to the inferential nature, aimed at the elucidation of how metonymic processes organize the experience and understanding of the world people. It takes into account the contributions of Lakoff (1987) about the approach of the Idealized Cognitive Models, and studies that prove the inferential role of metonymy in particular (Barcelona 2003, 2004, 200); Gibbs 1999; Panther & Thornburg 1999, Ibanez 2003 .) The analysis consists of a case study in order to observe the inferential face of the conceptual metonymy as is the process of building a particular concept through metonymic process. The results showed that conceptual metonymy has a range of socio-cultural.